Sterile corneal infiltrates after corneal collagen cross-linking: evaluation of risk factors - TOKER, AYŞE EBRU; ÇERMAN, EREN (WILEY, 2017)
Purpose: To evaluate possible risk factors leading to sterile corneal infiltrates following corneal collagen cross-linking (CXL). Methods: A total of 588 eyes of 459 patients treated with Epi-off (n = 461) or Epi-on (n = 127) CXL were retrospectively evaluated. Risk factors, including preoperative blepharitis and vernal conjunctivitis, the postoperative use of topical non-steroidal anti-inflammatory drugs (NSAIDs), as well as Kmax and pachymetry measurements, were assessed. In vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) analyses were performed in patients with sterile infiltrates. Results: Sterile infiltrates developed in 19 cases (3.2%). No patients in the Epi-on group developed sterile infiltrates. The evaluation of acceleration of the CXL procedure as a risk factor revealed no specific difference in the incidence of infiltrates among four different Epi-off groups (3 mW/cm(2)-30 min, 9 mW/cm(2)-10 min, 18 mW/cm(2)-5 min, 30 mW/cm(2)-4 min procedures; p > 0.05, all). Blepharitis, vernal conjunctivitis, Kmax and pachymetry were not identified as risk factors (p > 0.05). Postoperative use of NSAIDs was a significant contributor (p = 0.007), and it increased the chance of sterile infiltrates 4.09 times (95% CI, 1.463-11.428). In vivo confocal microscopy (IVCM) showed non-specific inflammation with dendritic cells at the epitheliumand at Bowman's layer. InAS-OCT, a hyper-reflective band at the level of the anterior stroma to a depth of 100-140 mu m was observed. Conclusion: The evaluation of the risk factors such as blepharitis, the use of NSAIDs, vernal conjunctivitis, the duration of CXL procedure and amount of light intensity showed that epithelial damage is possibly the common pathway in the pathogenesis, as no sterile infiltrates in Epi-on CXL occurred, and the postoperative use of NSAIDs increased the risk of developing sterile infiltrates about four times.
Keywords: collagen cross-linking; in vivo confocal microscopy; keratoconus; sterile infiltrate; IN-SITU KERATOMILEUSIS; DIFFUSE LAMELLAR KERATITIS; CONTACT-LENS USE; KERATOCONUS; RIBOFLAVIN; CELLS; PERFORATION; WEAR